(untitled) (Research, Society and Development, 2021)
Providing service has become an essential tool for enterprises seeking to highlight in such a competitive market. This paper presents data from a survey regarding the perception of customers for the footwear trade in the city of Sousa - PB, as well as from the analysis of the results brings theories about quality of care further enriching the contents. This research is descriptive and the approach is quantitative. The data collection was developed in shoe stores in the city of Sousa - PB, the studied sample are customers who attend such ventures through research tool the questionnaire. It aims to identify what consumers of the city of Sousa realize the care provided by companies in the retail industry shoes. The survey was conducted with 100 people, 58% of men and 42% women, the results are noticed the same number of people represented by the percentage of 36% define the service provided by footwear shops that are good and 36% are regular, totaling 72% of respondents. In conclusion, by analyzing the results, we can infer that customers of shoe stores in the city of Sousa-PB, realize a good quality in the care provided.